Sustainable Intensification in Agriculture: An Approach for Making Agriculture Greener and Productive - Shrestha, Jiban; Subedi, Subash; Timsina, Krishna Prasad; Subedi, Sudeep; Pandey, Meena; Shrestha, Aakriti; Shrestha, Sajina; Hossain, Mohammad Anwar (Journal of Nepal Agricultural Research Council, 2021)
Sustainable intensification of agriculture is a good approach for reducing the yield gap without exacerbating the current condition of the environmental components, which is a big challenge for agriculture in the modern world. This review provides a summary of the role and approaches of sustainable intensification in agriculture which offer ways to increase crop production and create long-term sustainability in agriculture production. The current demand for food has continued to rise as a result of the world's rapidly increasing population. In order to increase crop/food production, agricultural systems should be intensified by more sustainable practices, as well as by reforming existing production systems/techniques and diversifying them into newer and more profitable enterprises. Despite the heavy use of inputs, farmers have recently been unable to achieve optimal crop yields. The judicious use of agricultural inputs, combined with improved management techniques, is important for advancing sustainable intensification. New scientific techniques in agronomic practices, as well as improved farm mechanization, are helping to boost resource use efficiency in sustainable crop production. The sustainable agricultural intensification is necessary to increase the agricultural productivity under the changing and adverse climatic conditions while maintaining healthy production practices.